2016
DOI: 10.3847/2041-8205/830/1/l19
|View full text |Cite
|
Sign up to set email alerts
|

A Detection of the Integrated Sachs–wolfe Imprint of Cosmic Superstructures Using a Matched-Filter Approach

Abstract: We present a new method for detection of the integrated Sachs-Wolfe (ISW) imprints of cosmic superstructures on the cosmic microwave background, based on a matched filtering approach. The expected signal-to-noise ratio for this method is comparable to that obtained from the full crosscorrelation, and unlike other stacked filtering techniques it is not subject to an a posteriori bias. We apply this method to Planck CMB data using voids and superclusters identified in the CMASS galaxy data from the Sloan Digital… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 41 publications
4
80
0
Order By: Relevance
“…REVOLVER provides an option to remove RSD in the void positions through using density-field reconstruction prior to void finding (Nadathur et al 2019a,b), but this step has a negligibly small effect on the predicted lensing signal of voids, so is omitted here. Thus our void-finding procedure matches that previously used by Nadathur & Crittenden (2016).…”
Section: Boss Data and Void Catalogsupporting
confidence: 71%
“…REVOLVER provides an option to remove RSD in the void positions through using density-field reconstruction prior to void finding (Nadathur et al 2019a,b), but this step has a negligibly small effect on the predicted lensing signal of voids, so is omitted here. Thus our void-finding procedure matches that previously used by Nadathur & Crittenden (2016).…”
Section: Boss Data and Void Catalogsupporting
confidence: 71%
“…This would mean the primordial CS profile is even less significant than measured. Alternative models, which are not investigated here, may explain the slightly higher than expected causal relation between the observed and expected ISW of large voids seen in certain studies (Granett et al 2008;Cai et al 2014;Kovács et al 2017;Kovács 2017) but not all (Ilić et al 2013;Hotchkiss et al 2015;Nadathur & Crittenden 2016). Whether this is the case could be studied in future and would have implications for the predicted ISW contribution to the CS.…”
Section: Discussionmentioning
confidence: 99%
“…Early attempts at measuring the ISW signal using the cross-correlation method, include an analysis of the COBE CMB map by Boughn & Crittenden (2002) followed by detections of the signal using the WMAP CMB data, albeit often at relatively low to moderate levels of significance (Scranton et al 2003;Nolta et al 2004;Boughn & Crittenden 2004;Corasaniti et al 2005;Padmanabhan et al 2005;Giannantonio et al 2006;Cabré et al 2006;Rassat et al 2007; Raccanelli et al 2008;Granett et al 2009;Bielby et al 2010;Sawangwit et al 2010;Kovács et al 2013). Other studies have however claimed detections in the range of 3 − 5σ (Fosalba et al 2003;Fosalba & Gaztañaga 2004;Vielva et al 2006;McEwen et al 2006;Giannantonio et al 2008;Ho et al 2008;Granett et al 2008;Giannantonio et al 2012;Goto et al 2012;Planck Collaboration et al 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…Another common approach in measuring the ISW signal is by stacking of voids and super-clusters. Similar to the cross-correlation method, studies using this approach have obtained detection significances ranging from low to moderate (Granett et al 2015;Kovács et al 2017), to 3σ or higher (Pápai et al 2011;Nadathur & Crittenden 2016;Cai et al 2017;Planck Collaboration et al 2016c). Interestingly, a number of these studies have reported a signal with a higher amplitude than expected based on ΛCDM predictions.…”
Section: Introductionmentioning
confidence: 99%